The program of formation of psychological readiness for the professional activities of a locomotive driver - O. V. Leshchenko (Проблеми сучасної психології, 2017)
The article describes the program of formation of psychological readiness for the professional activities of a locomotive driver at the stage of primary and secondary professionalization. The purpose, structure, content of the program, the basic principles of work during the implementation of professional psychological training are defined. The advantages of professional psychological training as an effective method of forming psychological readiness for the professional activities of a locomotive engineer are mentioned. The effectiveness of the use of professional psychological training with the aim of forming emotional and volitional, motivational and personalityvalue components is indicated. The efficiency of the use of the training complex for enhancing the development of the psycho-physiological component of psychological readiness for the professional activities is confirmed. The effectiveness of the use of elements of the creative training of the CARUS system for the formation of a cognitive and operational component, which was divided into diagnostic and formative stages, is confirmed. The results of testing the effectiveness of the program of vocational and psychological training, which was carried out using the methods of mathematical statistics of Student’s t-criterion for independent and dependent samples, are presented. The results of the program realization on formation of psychological readiness for the professional activities at the stage of primary and secondary professionalization are indicated. It was established that the level of psychological readiness for the professional activities at the stage of primary and secondary professionalization was increased. It was found thatthere were significant differences between the experimental group before and after the experiment of primary and secondary professionalization.